Wastepaper modernism - Rosenberg, Joseph Elkanah (Oxford University Press, 2021)
From Henry James' fascination with burnt manuscripts to destroyed books in the fiction of the Blitz; from junk mail in the work of Elizabeth Bowen to bureaucratic paperwork in Vladimir Nabokov; modern fiction is littered with images of tattered and useless paper that reveal an increasingly uneasy relationship between literature and its own materials over the course of the twentieth-century. 0Wastepaper Modernism argues that these images are vital to our understanding of modernism, disclosing an anxiety about textual matter that lurks behind the desire for radically different modes of communication. At the same time that writers were becoming infatuated with new technologies like the cinema and the radio, they were also being haunted by their own pages. Having its roots in the late-nineteenth century, but finding its fullest constellation in the wake of the high modernist experimentation with novelistic form,
Literaturverzeichnis: Seite [199]-211
Keywords: Fiction / 20th century / History and criticism; Modernism (Literature) / History; Paper in literature; Fiction; Modernism (Literature); 1900-1999; Criticism; interpretation; etc; History